Identification of novel susceptibility loci and genes for prostate cancer risk: A transcriptome-wide association study in over 140,000 European descendants - Wu, Lang; Brenner, Hermann (Cancer research, 2019)
Genome-wide association studies have identified genetic variants associated with prostate cancer risk. However, these variants explain only a small fraction of the heritable component of prostate cancer risk, and the genes responsible for many of the identified associations remain unknown. To discover novel prostate cancer genetic loci and possible causal genes at previously identified risk loci, we performed a transcriptome-wide association study in 79,194 cases and 61,112 controls of European ancestry. Using data from the Genotype-Tissue Expression Project, we established genetic models to predict gene expression across the transcriptome for both prostate models and cross-tissue models and evaluated model performance using two independent datasets. We identified significant associations for 137 genes at P < 2.61×10-6, a Bonferroni-corrected threshold, including nine genes that remained significant at P < 2.61×10-6 after adjusting for all known prostate cancer risk variants in nearby regions. Of the 128 remaining associated genes, 94 have not yet been reported as potential target genes at known loci. We silenced 14 genes and many showed a consistent effect on viability and colony-forming efficiency in three cell lines. Our study provides substantial new information to advance our understanding of prostate cancer genetics and biology.
Gesehen am 03.09.2019